Foundation for an evidence‐informed algorithm for treating pelvic floor mesh complications: a review. (25th March 2018) - Cundiff, GW; Quinlan, DJ; van Rensburg, JA; Slack, M
Abstract: To address evidence gaps on the management of complications related to mesh in pelvic floor surgery, we created an evidence‐based algorithm that includes defining evidence gaps. We utilized the Delphi method within a panel of surgeons treating mesh complications to define a treatment strategy. The first round provided a list of clinically based postulates that informed a review expanding postulates to recommendations and included grading of the quality of evidence. A second round informed the final algorithm. While the quality of the available evidence is low, it provides a framework for planning diagnosis and management of mesh‐related complications. Tweetable abstract: Removal of mesh must balance resolution of complications with the risk of removal and recurrence of pelvic floor symptoms. Tweetable abstract: Removal of mesh must balance resolution of complications with the risk of removal and recurrence of pelvic floor symptoms.